Observations on seasonal occurrence in lymphomas with proven or presumed infectious etiology - Anagnostopoulos, Ioannis; Buck, Viktoria; Gerhard-Hartmann, Elena; Zamó, Alberto; Rosenwald, Andreas; Rosenfeldt, Mathias; Jöhrens, Korinna (Frontiers in Oncology, 2025)
IntroductionThere are relatively few studies on seasonal occurrence of lymphomas, most dealing with Hodgkin lymphoma (HL). Most studies were based on small datasets leading to partly conflicting patterns and results with only two using the large Surveillance, Epidemiology and End Results database. By doing this, the study on HL showed a peak incidence in March and the lowest in September, while the study on a broadly defined B-cell lymphoma group identified a peak in March and April. Among the hypotheses regarding seasonal occurrence of lymphomas, a potential infectious etiology has been proposed, at least for some patient subgroups.MethodsFor the present study, we used the files from one of Germany’s lymphoma reference centers and addressed not only seasonal occurrence but also whether lymphoma entities with proven or suspected infectious etiology were associated with a particular seasonal clustering. We also investigated whether the COVID-19 pandemic (period 2020-21) influenced any observed seasonal patterns. Our study population comprised 8,038 cases with primary diagnosis of classic HL (CHL) including 2,434 cases with Epstein-Barr virus (EBV) infection of the neoplastic cells, 1,402 cases of nodular lymphocyte predominant HL, 487 cases with cutaneous marginal zone lymphoma (MZL), 247 cases with pulmonary MZL, 451 cases with hairy cell leukemia (HCL) and 4,577 cases with diffuse large B cell lymphoma (DLBCL).Results and discussionOur data show that among HL only CHL exhibited seasonal fluctuation with a peak in the first quarter and a trough in the third quarter of the year. Similar seasonal patterns were observed in the nodular sclerosing CHL subtype and the younger patient age group (0–39 years). No seasonal fluctuation was identified in lymphomas with proven (EBV-positive CHL) or presumed infectious etiology (cutaneous and pulmonary MZL, HCL). COVID-19 pandemic did not significantly influence the seasonal occurrence patterns observed in CHL.